La aceleración de la luz en el vacío de un medio resistente - Monroy, Oscar (2023)
The study of the speed of light in the underlying vacuum of a resistant medium, as a mechanism for transmitting information, is complemented by the study of the acceleration of light in said medium. Applying the second order time derivative to the parametric equations, which represent the substrate in the underlying void of the resistant medium, a formula is obtained that would describe the acceleration with which the organized information is transmitted. The equation obtained varies with time for a given magnitude of the local vector quantum, as well as the resistance coefficient described by the substrate. Two possible symmetrical directions for the acceleration of light in the underlying vacuum of the resistant medium are considered, which would be correlated with the two possible directions of the local vector quantum. Ignoring the local vectorial quantum, the formula allows determining the maximum time and the minimum time in which the acceleration with which the information is transmitted in the system ceases. Furthermore, as a consequence of the second time derivative of the substrate associated with the underlying void of the resisting medium, and allowing for the correlations between the small excess/defect fluctuations of the opposing vector quanta and the opposing accelerations, a second quasi-equilibrium condition with which would explain the perception of light rays in a straight line in a resistant homogeneous medium. Finally, the results of the theory are applied to describe the acceleration with which a viral RNA particle replicates, showing that the formation of the nucleic acid decelerates inversely proportional to time. Also the theory predicts a maximum time interval and a minimum time interval in which the acceleration with which the nucleic acid is formed in an RNA viral particle is reduced to zero.